Analisis Game Bubur Ayam Express Sebagai Bentuk Advergame - Luvia Nisa Mutmainati (Journal of Animation and Games Studies, 2023)
Games in today's digital developments are no longer something that is difficult to reach, everyone can access games easily. This also affects the function and role of a game, where today's game is not only an entertainment medium but also an advertising medium. The role of games as an advertising medium is known as the advergame strategy, which is a combination of advertising and games. Games are considered capable of being an effective communication medium in communication between brands and consumers and are considered capable of increasing brand awareness of a product. One of them is Express Chicken Porridge Game. Game Bubur Ayam Express is an advertising medium for Sasa products produced by PT. Sasa Inti. Advergame has several types that differ from one type to another. The Bubur Ayam Express game uses an advergame type in the form of product placement where Sasa products are placed throughout the game and become part of the game's gameplay. The methodology used is qualitative with a visual analysis model.